HLA‐G promotes myeloid‐derived suppressor cell accumulation and suppressive activity during human pregnancy through engagement of the receptor ILT4. Issue 2 (9th December 2016) - Köstlin, Natascha; Ostermeir, Anna‐Lena; Spring, Bärbel; Schwarz, Julian; Marmé, Alexander; Walter, Christina B.; Poets, Christian F.; Gille, Christian
Abstract : In an in‐vitro study we showed that soluble HLA‐G (sHLA‐G) induced myeloid‐derived suppressor cells (MDSCs) from human peripheral blood mononuclear cells and increases their suppressive activity during pregnancy. MDSC expansion was mediated through the receptor ILT4 and accompanied by a phosphorylation of STAT3. Targeting MDSCs via HLA‐G could be a new strategy for treatment of immunologycal pregnancy complications. Abstract : Establishing and maintaining maternal‐fetal tolerance is essential for a successful pregnancy; failure of immunological adaptation to pregnancy leads to severe complications such as abortion or preterm delivery. Myeloid‐derived suppressor cells (MDSCs) are innate immune cells that suppress T‐cell responses, expand during pregnancy and thus may play a role in tolerance induction. Human leucocyte antigen G (HLA‐G) is a major histocompatibility complex (MHC) I molecule with immune‐modulatory properties, which is expressed during pregnancy. Here, we investigated the impact of HLA‐G on MDSCs accumulation and activation in pregnant women. We demonstrate that granulocytic MDSCs (GR‐MDSCs) express receptors for HLA‐G, namely immunoglobulin‐like transcript (ILT) 2 and 4, and that ILT4‐expression by GR‐MDSCs is regulated during pregnancy. Stimulation with soluble HLA‐G (sHLA‐G) increased suppressive activity of GR‐MDSCs, induced MDSCs from peripheral blood mononuclear cells (PBMCs) and led to phosphorylation of the signal transducer and activator of transcription 3 (STAT3) and induction of indoleamine‐2, 3‐dioxygenase (IDO) in myeloid cells. Effects of sHLA‐G on MDSC accumulation were mediated through ILT4. These results suggest an interaction between MDSCs and HLA‐G in humans as a potential mechanism for maintaining maternal‐fetal tolerance. Modulating MDSC function during pregnancy via HLA‐G might provide new opportunities for a therapeutic manipulation of immunological pregnancy complications.